Modification of eutectic Si in Al–Si alloys with Eu addition. (1st February 2015) - Li, J.H.; Wang, X.D.; Ludwig, T.H.; Tsunekawa, Y.; Arnberg, L.; Jiang, J.Z.; Schumacher, P.
Abstract: Al–5 wt.% Si-based alloys with 0.05 wt.% Eu addition were produced by controlled sand-casting and melt-spinning, respectively. The modification of eutectic Si caused by 0.05 wt.% Eu addition was investigated by thermal analysis, differential scanning calorimetry and multi-scale microstructure characterization techniques. In the case of controlled sand-casting, 0.05 wt.% Eu addition was found to modify the eutectic Si into a fibrous morphology. Multiply twinned Si particles were observed within eutectic Si. Furthermore, the Al2 Si2 Eu phase was also observed both in the vicinity of eutectic Si and within eutectic Si, which was believed to hinder Si growth. In the case of melt-spun samples, nanometer-sized Al2 Si2 Eu phases were observed. However, after controlled cooling in a differential scanning calorimeter, multiply twinned Si particles were observed. The formation of multiply twinned Si particles was attributed to the adsorption of Eu atoms along the 〈1 1 2〉Si growth direction of Si and at the intersection of two 1 1 1Si facets. Twinning was observed in both fundamentally different casting processes: controlled sand-casting and melt-spinning. This is fully consistent with the well-known poisoning of the twin plane re-entrant edge and the impurity-induced twinning modification mechanisms.